Crosstalk between lipocalin-2 and IL-6 in traumatic brain injury: Closely related biomarkers - Kim, Jae-Hong; Jeong, Han-Gil; Hyeon, Seung Jae; Park, Uiyeol; Oh, Won-Jong; Hwang, Junmo; Lim, Hyun-Ho; Ko, Pan-Woo; Lee, Ho-Won; Lee, Won-Ha; Ryu, Hoon; Suk, Kyoungho (Academic Press, 2025)
Clinical biomarkers are crucial for diagnosing and predicting outcomes in patients with traumatic brain injury (TBI). In this study, we performed an unbiased analysis of plasma proteins in acute TBI patients using bead-based multiplex assays and identified a strong positive correlation between LCN2 and IL-6 levels. Based on these findings, we hypothesized that LCN2 and IL-6 are closely related circulating biomarkers for TBI. Our previous and current studies demonstrate that the expression of LCN2, IL-6, and its receptors is upregulated in patients with chronic traumatic encephalopathy, in mouse models of traumatic and ischemic injury, and in an in vitro scratch injury model. Lcn2-deficiency reduced the injury-induced expression of IL-6 and its receptors in both animal and scratch injury models. These results suggest an augmented LCN2-dependent IL-6 signaling in the injured brain. As both LCN2 and IL-6 are secreted proinflammatory mediators, we further explored the possibility of cross-regulation between LCN2 and IL-6. In cultured glial cells, treatment with recombinant LCN2 protein enhanced the microglial expression of IL-6, while IL-6 protein treatment increased astrocytic LCN2 expression. Moreover, IL-6 expression and release were elevated in LCN2-overexpressing transgenic mice. Mechanistically, IL-6 enhanced astrocytic LCN2 expression through STAT3 signaling, while LCN2 upregulated microglial IL-6 expression through the NF-kappa B pathway. Taken together, our results suggest an important role of the LCN2-IL6 axis in amplifying neuroinflammation through a positive feedback loop in secondary brain injury conditions. Finally, this study implies the utility of LCN2 and IL-6 as closely related biomarkers for TBI diagnosis and prognosis.